The Association of Serum Uric Acid Levels and Various Uric Acid-Related Ratios with Insulin Resistance and Obesity: A Preliminary Study in Adolescents - Okan Dikker; Ayşe Aktaş; Mustafa Şahin; Murat Doğan; Hüseyin Dağ (MDPI AG, 2023)
Background: Studies have shown that serum uric acid levels and uric acid-related ratios, such as uric acid-to-albumin ratio (UAR), uric acid-to-creatinine ratio (UCR), uric acid-to-high-density lipoprotein cholesterol (HDL cholesterol) ratio (UHR), and uric acid-to-lymphocyte ratio (ULR), are associated with various diseases and their complications, and that these ratios can be used as biomarkers. In the current study, we aimed to investigate uric acid levels in obese adolescents and the relationship of uric acid-related ratios with insulin resistance and obesity for the first time in the literature. Methods: A total of 100 adolescents (60 obese and 40 healthy) aged 10-17 years were retrospectively included. Participants were assigned to two groups: the obese group and the healthy control group. Obesity was defined as a body mass index (BMI) >the 95th percentile for age and gender. Demographic and laboratory data (serum glucose, urea, creatinine, uric acid, albumin, aspartate aminotransferase (AST), alanine aminotransferase (ALT), C-reactive protein (CRP), total cholesterol, triglyceride, HDL cholesterol, thyroid-stimulating hormone (TSH), free T4 (fT4), insulin levels, and complete blood count) were obtained from the laboratory information management system. A homeostatic model of assessment for insulin resistance (HOMA-IR), low-density lipoprotein cholesterol (LDL cholesterol), and uric acid-related ratios were calculated. Results: Uric acid, UAR, UCR, and UHR levels of obese adolescents were significantly higher than the healthy group (p < 0.05). We found that HOMA-IR was positively correlated with uric acid, UAR, and UHR. No correlation was found between BMI and uric acid or uric acid-related ratios. We did not find any difference between the two groups in terms of ULR levels, and we did not find any correlation between BMI and HOMA-IR. Conclusion: High levels of serum uric acid, UAR, UCR, and UHR were associated with obesity. Furthermore, we found that uric acid, UAR, and UHR were positively correlated with insulin resistance.